(untitled) (American & British Studies Annual, 2013)
The article focuses on concepts of space in Thomas Hardy‘s Wessex novels, The Return of the Native, Tess of the d’Urbervilles and The Woodlanders. The theoretical approach used here is centred on two general categories of defining space. One is aesthetic expression of space, i.e. how space is perceived by the narrator or the characters themselves; this notion in some ways corresponds with smooth space as Deleuze and Guattari use this term to focus on the dynamics of forces in their Treatise on Nomadology in A Thousand Plateaus. The other category concerns mimetic aesthetics and space representation, i.e. how space is constructed with regard to a specific “reality,” a mediation which in some ways corresponds to Deleuze and Guattari’s category of space striation. Examples of both approaches will be shown in the essential conflict of the novels’ characters with respect to the environments they occupy. Attention will be devoted to the process of the characters’ assimilation into the environment, including their possible absorption by space.